2015
DOI: 10.1093/cvr/cvv187
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-bound Klotho is not expressed endogenously in healthy or uraemic human vascular tissue

Abstract: Using several independent and validated methods, we conclude that full-length, membrane-bound Klotho is not expressed in healthy or uraemic human vascular tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 55 publications
2
27
0
1
Order By: Relevance
“…In contrast, using real-time RT-PCR, with primers targeting different coding regions and various immune-detection techniques using several anti-α-klotho antibodies, Mencke et al . did not identify expression of α-klotho expression in the aorta of healthy individuals or in patients with CKD 57 , which is consistent with our results. Considering that expression of FGF-r3, a co-receptor for α-klotho, did not change, the likelihood that α-klotho is present in the walls of vessels and plays a role in resisting VC formation is moderate-to-low.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, using real-time RT-PCR, with primers targeting different coding regions and various immune-detection techniques using several anti-α-klotho antibodies, Mencke et al . did not identify expression of α-klotho expression in the aorta of healthy individuals or in patients with CKD 57 , which is consistent with our results. Considering that expression of FGF-r3, a co-receptor for α-klotho, did not change, the likelihood that α-klotho is present in the walls of vessels and plays a role in resisting VC formation is moderate-to-low.…”
Section: Discussionsupporting
confidence: 90%
“…Considering that expression of FGF-r3, a co-receptor for α-klotho, did not change, the likelihood that α-klotho is present in the walls of vessels and plays a role in resisting VC formation is moderate-to-low. This, however, does not deny the possibility that circulating α-klotho may serve as a humoral factor to protect against MAC 57 .…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, no α-Klotho or FGF23 mRNA was found in human aortic SMCs [60]. Table 2 also shows a number of other studies that failed to find α-Klotho expression in vascular SMCs or tissues [60,61,64,69,7377]. On the other hand, there are almost an equal number of studies where α-Klotho was detected in vascular tissues or SMCs [6264,7886,88,89] (Table 2).…”
Section: Roles Of Klotho In Vcmentioning
confidence: 99%
“…The present results clearly established that the Klotho gene is not expressed in the rat aorta. Some studies have indicated the presence of Klotho mRNA and protein in VSMCs with either decreased or increased expression in uremia, and some have found that Klotho was induced in the adventitia of the uremic rat aorta (17,29,37,48), whereas other investigations found no signs of Klotho being expressed in the aorta (35). The RT-PCR method used for the detection of Klotho mRNA might be too sensitive for the relevant demonstration of Klotho, as shown in the results of the present study, and factors related to poor specificity and sensitivity of the available Klotho antibodies for protein detection may all critically account for the discrepant findings in the actual literature, as recently discussed by our group (27).…”
Section: Uremicmentioning
confidence: 99%